2013
DOI: 10.1002/app.39571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of formulation and processing conditions on light shielding efficiency of thermotropic systems with fixed domains based on UV curing acrylate resins

Abstract: Within this study relationships between material formulation and processing parameters and the morphology (vacuole formation) of thermotropic systems with fixed domains (TSFD) for overheating protection purposes were investigated. Main aim was on improving light shielding efficiency of TSFD based on UV curable acrylate resins by optimization of selected key parameters including photo-initiator type and content, type of reactive diluent, radiation intensity/dose, and thermal treatment of layers during manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…For the annealed layers, the temperature-dependent behavior was inverted. Such kind of behavior was observed already in earlier studies [28][29][30]: TSFD without defects (like vacuoles or voids) showed a decrease in the solar hemispheric transmittance upon exceeding the threshold temperature. This behavior is consistent with the observed change in the relative refractive index (an increasing deviation from unity) between matrix and thermotropic additive upon exceeding the threshold temperature [28,30].…”
Section: Source Of Variationsupporting
confidence: 78%
See 4 more Smart Citations
“…For the annealed layers, the temperature-dependent behavior was inverted. Such kind of behavior was observed already in earlier studies [28][29][30]: TSFD without defects (like vacuoles or voids) showed a decrease in the solar hemispheric transmittance upon exceeding the threshold temperature. This behavior is consistent with the observed change in the relative refractive index (an increasing deviation from unity) between matrix and thermotropic additive upon exceeding the threshold temperature [28,30].…”
Section: Source Of Variationsupporting
confidence: 78%
“…This finding is supported by the observation that the addition of AT 11 was not effectual in order to enhance the difference between solar hemispheric transmittance at room temperature and at 70°C. For a layer lacking any AT 11 (specifically if that was layer M7A1-OTA-p3-RT-0.008 [29], which represents a treatment combination of AT 11: 0 mol kg -1 ; Indigo: 0 mol kg -1 ; treatment: RT; annealing: no; see Table 2), a solar hemispheric transmittance of 81.2 and 78.5% was achieved below and above the threshold temperature, respectively. Upon the application of an AT 11 concentration of 0.01 mol kg -1 , the solar hemispheric transmittance was recorded to be 81.9 and 81.1% below and above the threshold temperature, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations